2017
DOI: 10.1037/adb0000284
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to alcohol cues and responsible drinking statements within alcohol advertisements and public health campaigns: Relationships with drinking intentions and alcohol consumption in the laboratory.

Abstract: Both alcohol advertising and public health campaigns increase alcohol consumption in the short term, and this may be attributable to attentional capture by alcohol-related cues in both types of media. The present studies investigated the association between (a) visual attention to alcohol cues and responsible drinking statements in alcohol advertising and public health campaigns, and (b) next-week drinking intentions (Study 1) and drinking behavior in the lab (Study 2). In Study 1, 90 male participants viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…Participants in both districts highlighted alcohol promotion targeted to young people. Indeed, the alcohol industry adjusts their message according to the age, ethnicity, or income of the audience [61][62][63][64]. The advertisements targeted to the adult population were underreported by the participants, especially in the HID, where the presence of this type of promotion was higher than in the LID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in both districts highlighted alcohol promotion targeted to young people. Indeed, the alcohol industry adjusts their message according to the age, ethnicity, or income of the audience [61][62][63][64]. The advertisements targeted to the adult population were underreported by the participants, especially in the HID, where the presence of this type of promotion was higher than in the LID.…”
Section: Discussionmentioning
confidence: 99%
“…However, the alcohol industry has found strategies to promote their beverages. Future interventions may enforce and strengthen the laws to protect the population from alcohol promotion exposure given its association with higher alcohol consumption [24,62,[66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, con la ayuda de las redes no solo son usuarios los que pueden mostrar sus opiniones en este tipo de plataformas, sino que, desde las instituciones, el gobierno, los cuerpos de seguridad del estado, los medios de comunicación, así como los políticos pueden expresarse a través de estas redes, realizando campañas de concienciación y prevención del consumo de alcohol donde pueden llegar a todo el colectivo (Kersbergen y Field, 2017;Stautz et al, 2016). Se hace imprescindible, compartir las consecuencias que produce para la salud la ingesta incontrolada de alcohol tanto a corto como a largo plazo.…”
Section: Dicusión Y Conclusionesunclassified
“…Asimismo, el gobierno realiza a diario campañas de consumo responsable con la finalidad de reducir los daños que genera el consumo de alcohol y mejorar en consecuencia la salud pública. Este tipo de campañas se realizan a través de anuncios de prevención en televisión y mediante mensajes en carretera (Kersbergen y Field, 2017;Stautz, Brown, King, Shemilt, y Marteau, 2016).…”
unclassified
“…Some research found that anti-alcohol media messages were effective in reducing the urge to drink [6] or intentions to binge drink [7]. Other studies found no differences in intentions to drink after viewing anti-alcohol advertising versus alcohol advertising [8], and no differences in actual consumption after viewing anti-alcohol posters compared to no persuasion controls [9]. Again other studies have found that anti-alcohol media messages resulted in less negative attitudes towards alcohol [10], or even led to greater alcohol consumption [11].…”
Section: Introductionmentioning
confidence: 99%